2015
DOI: 10.1186/s12974-015-0373-x
|View full text |Cite
|
Sign up to set email alerts
|

Osthole confers neuroprotection against cortical stab wound injury and attenuates secondary brain injury

Abstract: BackgroundNeuroendoscopy is an innovative technique for neurosurgery that can nonetheless result in traumatic brain injury. The accompanying neuroinflammation may lead to secondary tissue damage, which is the major cause of delayed neuronal death after surgery. The present study investigated the capacity of osthole to prevent secondary brain injury and the underlying mechanism of action in a mouse model of stab wound injury.MethodsA mouse model of cortical stab wound injury was established by inserting a needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 72 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…Additionally, we also encapsulated Ost, an effective Chinese medicine monomer for Alzheimer's disease in our previous study. [19][20][21][22][23] It was hypothesized that Tf mediates the transport of Ost-Lip through the BBB via TfRs located on the surfaces of brain capillary endothelial cells, thereby increasing the accumulation of Ost in the brain. Several reports have indicated that Tf-modified liposomes could be used to transport drugs across the BBB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we also encapsulated Ost, an effective Chinese medicine monomer for Alzheimer's disease in our previous study. [19][20][21][22][23] It was hypothesized that Tf mediates the transport of Ost-Lip through the BBB via TfRs located on the surfaces of brain capillary endothelial cells, thereby increasing the accumulation of Ost in the brain. Several reports have indicated that Tf-modified liposomes could be used to transport drugs across the BBB.…”
Section: Resultsmentioning
confidence: 99%
“…The compound has attracted much attention due to its broad pharmacological effects, including its anti-inflammatory, anti-apoptotic, anti-oxidative stress, and neurotrophic factor-like properties. 19,20 Current research indicates that Ost has an improved effect on degenerative diseases of the central nervous system, such as Alzheimer's disease. [21][22][23] Ost can partially pass through the BBB as a small fatsoluble molecule, but its neuroprotective efficacy is limited by its poor solubility, poor stability, poor brain targeting, and low bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that EET attenuates IL-8 production in bronchial epithelial cells (15) and inflammation in the cardiovascular system (16). PLA2 has been suggested as an inflammatory marker closely associated with atherosclerosis (17). A combination of PLA2 and low-density lipoproteins in the blood generates a great amount of blood transportation, lecithin and free fatty acid oxidation, promoting atherosclerosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study, osthole can reduce Bax to Bcl-2 ratio in SWI. 66) It is a proven fact that immune cells and inflammatory are able to protect neural system in TBI. 67) Indeed, pro-inflammatory cytokines like IL-6, TNF-α and IL-1 all have the ability to protect neural cells.…”
Section: Discussionmentioning
confidence: 99%